The aesthetics of the grotesque in the art and narrative of manga (Palíndromo, 2023)
The article highlights the importance of the grotesque as an artistic and narrative resource in the expressions of Japanese comic culture, recognizing that the theme is multifaceted. Authors such as Maruo Suehiro, Kago Shintarou, Hino Hideshi, and Ito Junji are discussed in relation to this aesthetic, which has been explored for decades by Japanese comic artists, both in the production of popular manga and in more experimental and underground works. The article also explores manifestations of the grotesque in various aesthetic trends, such as Ero-Guro (erotic-grotesque), showing how these repertoires can be used to express complex and subversive themes, such as sexuality, violence, and social critique.
Keywords: Japanese comics (Manga); grotesque; aesthetics